Production of Lipase-catalyzed Structured Lipid from Olive Oil with Omega-3 Polyunsaturated Fatty Acids - Kahveci, Derya; Can, Asli; Ozcelik, Beraat (2009)
Acidolysis of olive oil with omega-3 (n-3) polyunsaturated fatty acids (PUFAs) was carried out to produce a structured lipid. Novozym 435 (R) from Candida antarctica was used as the biocatalyst. Response Surface methodology (RSM) was used to determine optimum conditions for lipase-catalyzed enrichment of olive oil. Three factors, 5 levels, central composite design was used. The effects of incubation time, temperature, and Substrate mole ratio on incorporation ratio (n-3 fatty acids/total fatty acids, %) were investigated. From the evaluation of response surface graphs, the optimal conditions for incorporation of long chain n-3 PUFAs into olive oil were 40-60 degrees C for temperature, 30-45 hr for reaction time, and 3:1-5:1 (n-3 fatty acids/olive oil) for substrate mole ratio. Experiments conducted under optimized conditions predicted by the model equation obtained from RSM yielded structured lipids with 50.8% n-3 PUFAs. This value agreed well with that predicted by the model. Oxidative stability tests showed that the product was more susceptible to oxidation than unmodified olive oil. Antioxidant addition improved the oxidative stability of the product.